Surgical parameters influence paediatric knee kinematics and cartilage stresses in anterior cruciate ligament reconstruction: Navigating subject‐specific variability using neuromusculoskeletal‐finite element modelling analysis - Dastgerdi, Ayda Karimi; Esrafilian, Amir; Carty, Christopher P.; Nasseri, Azadeh; Barzan, Martina; Korhonen, Rami K.; Astori, Ivan; Hall, Wayne; Saxby, David John (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2025)
Purpose Anterior cruciate ligament (ACL) rupture is increasingly common in paediatric and adolescent populations, typically requiring surgical ACL reconstruction (ACLR) to restore knee stability. However, ACLR substantially alters knee biomechanics (e.g., motion and tissue mechanics) placing the patient at elevated risk of early‐onset knee osteoarthritis. Methods This study employed a linked neuromusculoskeletal (NMSK)‐finite element (FE) model to determine effects of four critical ACLR surgical parameters (graft type, size, location and pre‐tension) on tibial articular cartilage stresses in three paediatric knees of different sizes during walking. Optimal surgical combinations were defined by minimal kinematic and tibial cartilage stress deviations in comparison to a corresponding intact healthy knee, with substantial deviations defined by normalized root mean square error (nRMSE) > 10%. Results Results showed unique trends of principal stress deviations across knee sizes with small knee showing least deviation from intact knee, followed by large‐ and medium‐sized knees. The nRMSE values for cartilage stresses displayed notable variability across different knees. Surgical combination yielding the highest nRMSE in comparison to the one with lowest nRMSE resulted in an increase of maximum principal stress on the medial tibial cartilage by 18.0%, 6.0% and 1.2% for small, medium and large knees, respectively. Similarly, there was an increase of maximum principal stress on lateral tibial cartilage by 11.2%, 4.1% and 12.7% for small, medium and large knees, respectively. Knee phenotype and NMSK factors contributed to deviations in knee kinematics and tibial cartilage stresses. Although optimal surgical configurations were found for each knee size, no generalizable trends emerged emphasizing the subject‐specific nature of the knee and neuromuscular system. Conclusion Study findings underscore subject‐specific complexities in ACLR biomechanics, necessitating personalized surgical planning for effective restoration of native motion and tissue mechanics. Future research should expand investigations to include a broader spectrum of subject‐specific factors to advance personalized surgical planning. Level of Evidence Level III.